Contact-events and associated head acceleration events in semi-elite women`s rugby union: A competition-wide instrumented mouthguard study - Roe, G.; Sawczuk, T.; Starling, L.; Gilthorpe, M. S.; Salmon, D.; Falvey, É.; Hendricks, S.; Rasmussen, K.; Stokes, K.; Tooby, J.; Owen, C.; Tucker, R.; et al. (Journal of Sports Sciences, 2025)
This study aimed to quantify contact-events and associated head acceleration event (HAE) probabilities in semi-elite women`s rugby union. Instrumented mouthguards (iMGs) were worn by players competing in the 2023 Farah Palmer Cup season (13 teams, 217 players) during 441 player-matches. Maximum peak linear acceleration (PLA) and peak angular acceleration (PAA) per-event were used as estimates of in vivo HAE (HAEmax), linked to video analysis-derived contact-events and analysed using mixed-effects regression. Back-rows had the highest number of contact-events per full-match (44.1 [41.2 to 47.1]). No differences were apparent between front-five and centres, or between half-backs and outside-backs. The probability of higher HAEmax occurring was greatest in ball-carries, followed by tackles, defensive rucks and attacking rucks. Probability profiles were similar between positions but the difference in contact-events for each position influenced HAEmax exposure. Overall, most HAEmax were relatively low. For example, the probability of a back-row experiencing a PLA HAEmax =25g was 0.045 (0.037-0.054) for ball carries (1 in every 22 carries), translating to 1 in every 2.3 full games. This study presents the first in-depth analysis of contact-events and associated HAEmax in semi-elite women`s rugby union. The HAEmax profiles during contact-events can help inform both policy and research into injury mitigation strategies.